Gandharan Deities in the 4th Century BCE - 2nd Century CE - Rehman, Aman-ur (Ancient Pakistan, 2021)
It is a privilege to have been invited to give a talk on my collection of seals, sealings and tokens and to present my views on the iconography of deities in Gandhara during the 4th century BCE - 2nd century CE period.